2015
DOI: 10.1242/jeb.119321
|View full text |Cite
|
Sign up to set email alerts
|

Myoglobin oxygen affinity in aquatic and terrestrial birds and mammals

Abstract: Myoglobin (Mb) is an oxygen binding protein found in vertebrate skeletal muscle, where it facilitates intracellular transport and storage of oxygen. This protein has evolved to suit unique physiological needs in the muscle of diving vertebrates that express Mb at much greater concentrations than their terrestrial counterparts. In this study, we characterized Mb oxygen affinity (P 50 ) from 25 species of aquatic and terrestrial birds and mammals. Among diving species, we tested for correlations between Mb P 50 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 102 publications
(107 reference statements)
1
16
0
Order By: Relevance
“…The results, however, demonstrated that the oxygen affinity of Mb was not significantly changed during the adaptation process. The P 50 values for extant animals were reported previously, and indicated that deep-sea and land animal Mbs had similar O 2 -binding affinities 49 , which was consistent with the present results. This seems to be reasonable because whales adsorb O 2 from the air on the sea surface, where p O 2 condition is similar to that for land animals, and enhancement of the O 2 affinity is not beneficial for the deep-sea adaptation.…”
Section: Resultssupporting
confidence: 93%
“…The results, however, demonstrated that the oxygen affinity of Mb was not significantly changed during the adaptation process. The P 50 values for extant animals were reported previously, and indicated that deep-sea and land animal Mbs had similar O 2 -binding affinities 49 , which was consistent with the present results. This seems to be reasonable because whales adsorb O 2 from the air on the sea surface, where p O 2 condition is similar to that for land animals, and enhancement of the O 2 affinity is not beneficial for the deep-sea adaptation.…”
Section: Resultssupporting
confidence: 93%
“…High Mb content is known to increase oxygen-storage capacity and may also promote intracellular oxygen transport (Wittenberg and Wittenberg, 2006;Koch and Britton, 2008;Mirceta et al, 2013). Diving animals rely heavily on Mb O 2 stores, rather than capillaries, for mitochondrial O 2 supply during dives, and dive duration is positively correlated with Mb concentration (Reed et al, 1994;Butler and Jones, 1997;Kooyman and Ponganis, 1998;Dolar et al, 1999;Helbo and Fago, 2012;Mirceta et al, 2013;Wright and Davis, 2015). Torrent ducks have nearly four times the Mb content reported for nonaquatic birds (Pages and Planas, 1983;Butler and Jones, 1997;Kooyman and Ponganis, 1998;Wright and Davis, 2015), suggesting that they may also have a strong dive capacity.…”
Section: High Mb Content In Torrent Ducksmentioning
confidence: 99%
“…The hemeprotein myoglobin (Mb) is expressed in the muscle tissue of vertebrates (1)(2)(3)(4), where it functions to store oxygen (2)(3)(4)(5)(6)(7)(8). A high level of muscle Mb expression allows certain mammals to hold their breath for longer time periods, as occurs in diving mammals like whales, seals, or dolphins (9)(10)(11)(12). Genetic depletion of Mb in mice induces several compensatory mechanisms that partly overcome its loss and thus leads to viable and fertile mice (13).…”
mentioning
confidence: 99%